Edukasi Pemanfaatan Lahan Sempit Masyarakat Desa Sunggumanai Kabupaten Gowa melalui Green Family (Meningkatkan Kesadaran Lingkungan) - Irwan Alim; Aldy Nurdiansyah B; Riski Riski (Yayasan Literasi Sains Indonesia, 2026)
This community service activity, carried out by students from the Faculty of Social and Political Sciences, Unismuh Makassar, aims to raise environmental awareness through a program to utilize narrow land in densely populated residential areas. Using a descriptive qualitative approach, this activity is carried out through participatory dialogue with residents, education on the importance of environmental conservation, and direct planting of various types of vegetables as a form of real actualization. Through this approach, the community not only gains knowledge but also directly experiences the process of managing limited space into a productive area. The results of the activity indicate that the utilization of narrow land has a positive impact on the community, both environmentally and socioeconomically. Residents experience direct benefits in the form of the availability of fresh vegetables that can be consumed themselves or sold for additional income. The local government also provides full support because this program is considered capable of providing concrete education, observable results, and a real contribution to increasing environmental awareness. This program also shows potential for sustainability as the community is starting to be motivated to continue and expand the practice.